2016
DOI: 10.1038/eye.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings in giant cell arteritis

Abstract: PurposeGiant cell arteritis (GCA) is a systemic vasculitis that affects medium-to-large-caliber arteries. Early diagnosis and treatment is essential as involvement of the ophthalmic artery or its branches may cause blindness. Radiographic findings may be variable and non-specific leading to delay in diagnosis. We conducted a review of the literature on neuroimaging findings in GCA and present a retrospective case series from tertiary-care ophthalmic referral centers of three patients with significant neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
1
28
1
Order By: Relevance
“…Peripheral musculoskeletal manifestations are reported in GCA and PMR, including arthritis, swelling of the distal extremities with pitting oedema (more likely PMR than GCA), tenosynovitis and carpal tunnel syndrome [33], although their presence should alert the clinician to possible alternative diagnoses such as rheumatoid arthritis. Due to the wide ranging phenotype, clinicians require a high index of suspicion for GCA [29] because atypical presentations of GCA may delay diagnosis and lead to further complications [34].…”
Section: Clinical Presentation-systemic Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral musculoskeletal manifestations are reported in GCA and PMR, including arthritis, swelling of the distal extremities with pitting oedema (more likely PMR than GCA), tenosynovitis and carpal tunnel syndrome [33], although their presence should alert the clinician to possible alternative diagnoses such as rheumatoid arthritis. Due to the wide ranging phenotype, clinicians require a high index of suspicion for GCA [29] because atypical presentations of GCA may delay diagnosis and lead to further complications [34].…”
Section: Clinical Presentation-systemic Featuresmentioning
confidence: 99%
“…A contrast-enhanced high-resolution MRI can demonstrate arterial wall thickening with peri-adventitial and mural contrast enhancement [1]. Neuroimaging is not usually required for patients with a typical presentation of GCA, but some patients may have already undergone the investigation previously [34]. Studies have shown MRI to have a sensitivity of 68-89% and a specificity of 73-97% [1].…”
Section: Research In Other Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging is not usually required in patients with typical presentations of giant cell arteritis (GCA) and when performance is generally normal [18]. However, some patients have already undergone imaging before neuro-ophthalmic evaluation, and these studies may be abnormal.…”
Section: Arteritic Anterior Ischemic Optic Neuropathy (Aaion)mentioning
confidence: 99%
“…MRI findings may hold some diagnostic value in distinguishing between A-AION as in GCA and in nonarteritic AION, in which they are typically normal. Differential diagnosis for these MRI findings can lead to inappropriate testing and delay diagnosis and treatment [18].…”
Section: Optic Chasmal Enhancementmentioning
confidence: 99%